Implementation of Criminal Case Trials Through a Teleconference by Prosecutors with a Progressive Legal Approach - Muhamad Mahrus Setia Wijaksana (Journal of Morality and Legal Culture, 2020)
The development of technology in the era of the 4.0 industrial Revolution, characterized by digitalization until covering the realm of criminal law, was affected by the activity of law enforcement. Moreover, this time crowded about criminal trials through teleconference in the middle increasingly the mass of pandemic spread covid-19 which of course also affects the duties and authority of the prosecutor. The study focuses on analyzing the implementation of the trial in a teleconference by prosecutors with a progressive legal approach, highlighting the law as "not only rules and logic but also behavior." This research uses the socio-legal approach. The results showed that the legal arrangements related to criminal proceedings through the teleconference were still scattered in various regulations and the double implications of prosecutors. As for the implementation of the trial teleconference by prosecutors from the legal side of progressive measured from two things, first behavior seen in the trial that met many challenges, second is measured from an understanding of a progressive order/following the dynamics of community development. But the future also needs to be re-evaluated every weakness of existing current and formulated standard operational procedures and detailed legal provisions of the proceedings through the teleconference selectively.